2023
DOI: 10.1038/s41591-023-02326-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tau-targeting antisense oligonucleotide MAPTRx in mild Alzheimer’s disease: a phase 1b, randomized, placebo-controlled trial

Abstract: Tau plays a key role in Alzheimer’s disease (AD) pathophysiology, and accumulating evidence suggests that lowering tau may reduce this pathology. We sought to inhibit MAPT expression with a tau-targeting antisense oligonucleotide (MAPTRx) and reduce tau levels in patients with mild AD. A randomized, double-blind, placebo-controlled, multiple-ascending dose phase 1b trial evaluated the safety, pharmacokinetics and target engagement of MAPTRx. Four ascending dose cohorts were enrolled sequentially and randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 65 publications
(70 reference statements)
3
44
0
1
Order By: Relevance
“…To evaluate proof of mechanism of the study drug, levels of t-tau and p-tau181 in the CSF were evaluated. Results from the placebo-controlled MAD study have been previously reported . Briefly, the placebo group maintained stable levels of both analytes throughout the duration of the MAD period, in line with prior natural history studies, whereas the BIIB080-treated groups demonstrated dose-dependent decreases in both analytes during the 13-week treatment period (Figure 2, eTables 6 and 7, and eFigure 2 in Supplement 3).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…To evaluate proof of mechanism of the study drug, levels of t-tau and p-tau181 in the CSF were evaluated. Results from the placebo-controlled MAD study have been previously reported . Briefly, the placebo group maintained stable levels of both analytes throughout the duration of the MAD period, in line with prior natural history studies, whereas the BIIB080-treated groups demonstrated dose-dependent decreases in both analytes during the 13-week treatment period (Figure 2, eTables 6 and 7, and eFigure 2 in Supplement 3).…”
Section: Resultssupporting
confidence: 83%
“…5 Clinically, a multiple ascending-dose (MAD) phase 1b study was completed in participants with mild AD, with the primary objective of evaluating the safety and tolerability of BIIB080. As previously published, 6 BIIB080 was generally well tolerated. The majority of adverse events were mild or moderate in severity, of which the most common were headache, back pain, and post-lumbar puncture syndrome.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…If AD is a consequence of first tau spread and then production, it will be crucial for these immunotherapies to be administered early in the AD process to halt the widespread transmission of tau before accelerated local production can occur. In contrast, therapies that act to reduce intracellular tau concentration should be effective in slowing AD progression across the AD continuum, regardless of whether widespread tau transmission has occurred [53].…”
Section: Discussionmentioning
confidence: 99%